Burden and depression among informal caregivers of visually impaired patients in Mexico. Issue 3 (July 2022) - Ruiz-Lozano, Raul E.; de la Rosa-Pacheco, Sylvia; Hernández-Camarena, Julio C.; Garza-Garza, Lucas A.; Davila-Cavazos, Osvaldo; Dominguez-Varela, Irving A.; Quiroga-Garza, Manuel E.; Rodriguez-Garcia, Alejandro
Abstract: Background: The needs of informal caregivers who provide care to family relatives with visual impairment are often neglected, resulting in burden and depression. Objective: To determine the degree of burden and the prevalence of major depression experienced by caregivers, defined as non-paid family relatives, of legally blind individuals in a Mexican population. Methods: Observational, single-center, cross-sectional study in adults providing care to their family relatives with visual impairment (visual acuity ≤ 20/200 in the best eye for at least 3 months). According to visual impairment degree, care provided included activities of daily living (ADL) and instrumental ADL. Burden of care was evaluated with the Zarit burden interview (ZBI)-22 and the prevalence of major depression was determined by the patient health questionnaire (PHQ)-9. Results: 115 patients and 115 caregivers were included. Male caregivers had significantly higher ZBI-22 (28.7 ± 15.5 vs. 19.2 ± 12.6, p = 0.001) and PHQ-9 (10.0 ± 5.5 vs. 5.3 ± 5.1, p < 0.001) scores than females. Likewise, parent caregivers of adult children and the hours of daily care were significantly associated with higher burden and depression scores. A significant linear correlation between ZBI-22 and PHQ-9 scores in caregivers was also found (r = 0.649, p < 0.001). Conclusions: Male caregivers, parent caregivers of adult children, and caregivers providing greater hours of care were at higher risk of burden and depression. Upon diagnosis of visual impairment, adults providing care to visually impaired family relatives should be screened for burden and depression and referred to a mental health specialist when necessary. Tailored interventions targeting the caregivers' needs are required to reduce burden and depression. Highlights: The prevalence of blind individuals, due to increasing life expectancy, is continuously rising. A significant number of family relatives providing care to patients with visual impairment are depressed.. Male parents at care of blind adult children were more likely to experience burden and depression. Effective strategies are required to manage and reduce the burden and depression among caregivers of blind individuals.